Can immune gene silencing via dsRNA feeding promote pathogenic viruses to control the globally invasive Argentine ant?. Issue 2 (9th December 2022) - Felden, Antoine; Dobelmann, Jana; Baty, James W.; McCormick, Joseph; Haywood, John; Lester, Philip J.
Abstract: Pest control methods that can target pest species with limited environmental impacts are a conservation and economic priority. Species‐specific pest control using RNA interference is a challenging but promising avenue in developing the next generation of pest management. We investigate the feasibility of manipulating a biological invader's immune system using double‐stranded RNA (dsRNA) in order to increase susceptibility to naturally occurring pathogens. We used the invasive Argentine ant as a model, targeting the immunity‐associated genes Spaetzle and Dicer‐1 with dsRNA. We show that feeding with Spaetzle dsRNA can result in partial target gene silencing for up to 28 days in the laboratory and 5 days in the field. Dicer‐1 dsRNA only resulted in partial gene knockdown after 2 days in the laboratory. Double‐stranded RNA treatments were associated with significant gene expression disruptions across immune pathways in the laboratory and to a lower extent in the field. In total, 12 viruses and four bacteria were found in these ant populations. Some changes in viral loads in dsRNA‐treated groups were observed. For example, Linepithema humile Polycipivirus 2 (LhuPCV2) loads increased after 2 days of treatment with Spaetzle and Dicer‐1 dsRNA treatments in the laboratory. After treatment with the dsRNA in the field, after 5 days the virus Linepithema humile toti‐like virus 1 (LhuTLV1) was significantly more abundant. However, immune pathway disruption did not result in a consistent increase in microbial infections, nor did it alter ant abundance in the field. Some viruses even declined in abundance after dsRNA treatment. Our study explored the feasibility of lowering a pest's immunity as a control tool. We demonstrate that it is possible to alter immune gene expression of pest species and pathogen loads, although in our specific system the affected pathogens did not appear to influence pest abundance. We provide suggestions on future directions for dsRNA‐mediated immune disruption in pest species, including potential avenues to improve dsRNA delivery as well as the importance of pest and pathogen biology. Double‐stranded RNA targeting immune function might be especially useful for pest control in systems in which viruses or other microorganisms are prevalent and have the potential to be pathogenic.